Multi-field inflation from single-field models. Issue 8 (20th August 2021) - Bojowald, Martin; Brahma, Suddhasattwa; Crowe, Sean; Ding, Ding; McCracken, Joseph
Abstract: Quantization implies independent degrees of freedom that do not appear in the classical theory, given by fluctuations, correlations, and higher moments of a state. A systematic derivation of the resulting dynamical systems is presented here in a cosmological application for near-Gaussian states of a single-field inflation model. As a consequence, single-field Higgs inflation is made viable observationally by becoming a multi-field model with a specific potential for a fluctuation field interacting with the inflaton expectation value. Crucially, non-adiabatic methods of semiclassical quantum dynamics reveal important phases that can set suitable initial conditions for slow-roll inflation (in combination with the uncertainty relation), and then end inflation after the observationally preferred number of e-folds. New parameters in the interaction potential are derived from properties of the underlying background state, demonstrating how background non-Gaussianity can affect observational features of inflation or, conversely, how observations may be used to understand the quantum state of the inflaton.